2013
DOI: 10.1186/1740-3391-11-4
|View full text |Cite
|
Sign up to set email alerts
|

A tryptophan-rich breakfast and exposure to light with low color temperature at night improve sleep and salivary melatonin level in Japanese students

Abstract: BackgroundEpidemiological studies in Japan have documented an association between morning type and a tryptophan-rich breakfast followed by exposure to sunlight in children. The association may be mediated by enhanced melatonin synthesis, which facilitates sleep at night. However, melatonin is inhibited by artificial light levels with high color-temperature common in Japanese homes at night. In this study, we investigated whether a combination of tryptophan-rich breakfast and light with low color-temperature at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 30 publications
3
32
1
3
Order By: Relevance
“…Exposure to sunlight or lighting by mobile phones in the morning is possible to trigger synthesis of serotonin in the pineal body (Rosenthal et al, 1997;Wada et al, 2013). This action is hypothesized to occur mainly in the morning, because the amount of tryptophan consumed with supper has neither significant effects on Moriningness-Eveningness (M-E) scores nor an effect on sleep habits, as shown by another study on young Japanese children performed in 2005 (Harada et al, 2012).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Exposure to sunlight or lighting by mobile phones in the morning is possible to trigger synthesis of serotonin in the pineal body (Rosenthal et al, 1997;Wada et al, 2013). This action is hypothesized to occur mainly in the morning, because the amount of tryptophan consumed with supper has neither significant effects on Moriningness-Eveningness (M-E) scores nor an effect on sleep habits, as shown by another study on young Japanese children performed in 2005 (Harada et al, 2012).…”
Section: Introductionmentioning
confidence: 89%
“…Light conditions are most effective zeitgeber for human circadian clock (Wada et al, 2013). Exposure to sunlight or lighting by mobile phones in the morning is possible to trigger synthesis of serotonin in the pineal body (Rosenthal et al, 1997;Wada et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Morning typed members would be speculated to changed to more-evening typed ones, because the shortage of morning sun lights occurred due to later sun rise in this season of late November and early December. Tryptophan included in the cows' milk could be metabolized to serotonin in the morning and serotonin again would be synthesized to melatonin at night Nakade et al, 2009Nakade et al, , 2012Wada et al, 2013;Harada et al, 2016) in the pineal of brains of the participants. Therefore, the sleep latency seems to become shorter during the intervention due to the melatonin synthesis which has been known as the natural sleep inducer (Bruni et al, 2015) based on the cow milk intake at the breakfast.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that protein intake at breakfast would raise blood tryptophan levels, and that this would, through the synthesis of serotonin (an anti-depressive agent), be effective in promoting mental health and morning-type habits and also, following synthesis into melatonin, which promotes sleep onset at night (Harada et al, 2007;Nakade et al, 2009Nakade et al, , 2012Wada et al, 2013). For Japanese children, drinking cows' milk at breakfast is an important source of tryptophan and could, on the basis of a questionnaire study (Takeuchi et al, 2014), be supposed to promote the mental and sleep health, although there have been no intervention studies to test this hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…For example, better mental health can be promoted by the nutritionally rich breakfast (including protein resource as tryptophan supply: Harada et al, 2007;Nakade et al, 2009Nakade et al, , 2012Harada et al, 2012;Wada et al, 2013) based on basic questionnaire studies and intervention studies. On the relationship between the mental health and the frequency to take breakfast in Korea, the data were obtained from the 2013 Korean Community Health Survey; a total of 207,710 survey participants aged 20 years or over were studied.…”
Section: Breakfast and Mental Health In Childrenmentioning
confidence: 99%